(untitled) (Fiep Bulletin - online, 2011)
In Brazil, the mobilization of entities and professionals towards denouncing child abuse has only begun over the last few decades, with the appearance of representative political forces and instances dedicated to prevention and denounce. With these initiatives, child abuse cases have become more visible for society, making the notification of suspected or confirmed cases mandatory. This work was thus aimed at identifying, according to each health professional’s experiences, the types of abuse on hospitalized children, their aggressors and the most affected body region. It’s a quantitative exploratory descriptive study, performed in the Hospital da Criança Santo Antônio/RR, with a population of 235 health professionals. The results show a predominance of female gender with 179 (76.2%) aged 31 to 35 with a total of 63 (26.8%). As for professional formation, 150 (63.9%) were nursing assistants and technicians, 38 (16.2%) doctors, 35 (14.8%) nurses, 07 (3.9%) social assistants and 05 (2.1%) psychologists. Most professionals (27.72%) considered the mother to be the main abuser, followed by the father with 26.36%. When analyzing body region, 26.55% identified limbs and pelvic waist, followed by head and neck (22.94%).